High-Fat Diet Promotes Macrophage-Mediated Hepatic Inflammation and Aggravates Diethylnitrosamine-Induced Hepatocarcinogenesis in Mice - Fu, Huiying; Tang, Biqiang; Lang, Jiali; Du, Yueguang; Cao, Beibei; Jin, Lushuai; Fang, Mingsun; Hu, Zhiming; Cheng, Changpei; Liu, Xia; Shou, Qiyang (Frontiers in Nutrition, 2020)
It has been reported that diet and nutrition play important roles in the occurrence and development of hepatocellular carcinoma (HCC). In this study, we investigated the potential tumor-promoting mechanisms of a high-fat diet (HFD) in mice with dietondiethylnitrosamine (DEN)-induced hepatocarcinogenesis. HFD significantly decreased the survival rate and induced severe liver dysfunction in DEN-induced mice, as indicated by increased serum glutamic-pyruvic transaminase (ALT), glutamic oxalacetic transaminase (AST), and alkaline phosphatase (ALP) levels and increased liver index, liver nodule count, and γ-glutamyltransferase (γ-GT) activity. Moreover, an increased number of fat droplets and HCCs were found in the livers of the HFD mice, who displayed little collagen in and around the liver cancer groove and the infiltration of large number of inflammatory cells, such as macrophages, compared with the control mice. HFD also significantly increased proliferating cell nuclear antigen (PCNA), nuclear factor-κB (NF-κB), cyclin D1, tumor necrosis factor (TNF), and interleukin-1 (IL-1) expression levels in the liver. In vitro, we found that the inducible nitric oxide synthase (iNOS) percentage increased in macrophages after palmitic acid treatment, as well as the secretion of inflammatory factors and cytokines such as interleukin-6(IL-6), interleukin-10(IL-10), CCL2, Interferon γ (IFN-γ), and TNF. Thus, our results demonstrate that an HFD may promote DEN-induced hepatocarcinogenesis in mice by destroying liver function and enhancing the inflammatory response by recruiting and polarizing macrophages in the liver. This study could therefore provide new insights into the tumor promoting effects of an HFD in HCC.